Marx, Honneth and the Tasks of a Contemporary Critical Theory - Deranty, Jean-Philippe (2013)
In this paper, I consider succinctly the main Marxist objections to Honneth’s model of critical social theory, and Honneth’s key objections to Marx-inspired models. I then seek to outline a rapprochement between the two positions, by showing how Honneth’s normative concept of recognition is not antithetical to functionalist arguments, but in fact contains a social-theoretical dimension, the idea that social reproduction and social evolution revolve around struggles around the interpretation of core societal norms. By highlighting the social theoretical side of recognition, one can outline a model of critical social theory that in fact corresponds to the descriptive and normative features outlined by Marx himself. However, the price of this rapprochement for Honnethian critical theory is a greater emphasis on the division of labour as the central mechanism of social reproduction.
Keywords: Division of labour; Social labour; Functionalism; Recognition; Critical Theory; Honneth; Marx